Методика створення математичної моделі віртуального машинно-тракторного агрегату - Мельник, В.; Анікєєв, О.; Чигрина, С.; Шуляк, М.; Купін, О. (Науковий журнал «Інженерія природокористування», 2020)
The issue of developing a type of mobile energy means (MES), as well as a unified methodology for its formation, as an organizational basis for tractor policy is considered.The basic basis for completing the optimal options for units is the traction parameters of tractors, which are included in the system of their classification. To date, not only the final version of the type of mobile energy means is lacking, but also a unified methodology for its formation.Based on the results of scientific works of scientists who developed the classification of tractors, we propose our own version of modeling the functionality of traction-energy and traction concepts, the classification of which is based on GOST 27021-86, respectively. This technique reveals the essence of creating a mathematical model of a virtual MTA for traction tractors.For the development of the methodology, the initial data were formed on the basis of completing the units for performing nine basic technological operations in the conventional farm. For each of the units at all operations, the following calculations were performed: productivity per hour of the main time, fuel consumption per unit of work, the actual utilization factor of the tractor weight and specific traction resistance of the unit working bodies.After the performed calculations for all technological operations, a functional relationship was established between the productivity of the MTA per hour of the main time, the utilization factor of the tractor weight and the operating weight of the tractor. And also a functional relationship was established between fuel consumption per unit of work, the utilization factor of the tractor weight and the operating weight of the tractor.Functional connections were obtained using the Lab fit program by constructing 3d surfaces. After constructing all 3d surfaces, analytical dependences were obtained with the formation of coefficients a and b for all technological operations.The obtained analytical dependencies for productivity and fuel consumption are the final mathematical model of a virtual MTA, which takes into account the weight of the tractor as the main parameter of tractors of the traction concept, and its relationship with the productivity and fuel consumption (through the use of appropriate coefficients) when performing a specific technological operation.